CAR T-cells targeting FGFR4 and CD276 simultaneously show potent antitumor effect against childhood rhabdomyosarcoma - Tian, Meijie; Wei, Jun S.; Cheuk, Adam Tai-Chi; Milewski, David; Zhang, Zhongmei; Kim, Yong Yean; Chou, Hsien-Chao; Liu, Can; Badr, Sherif; Pope, Eleanor G.; Rahmy, Abdelrahman; Wu, Jerry T.; et al. (Nature communications, 2024)
Chimeric antigen receptor (CAR) T-cells targeting Fibroblast Growth Factor Receptor 4 (FGFR4), a highly expressed surface tyrosine receptor in rhabdomyosarcoma (RMS), are already in the clinical phase of development, but tumour heterogeneity and suboptimal activation might hamper their potency. Here we report an optimization strategy of the co-stimulatory and targeting properties of a FGFR4 CAR. We replace the CD8 hinge and transmembrane domain and the 4-1BB co-stimulatory domain with those of CD28. The resulting CARs display enhanced anti-tumor activity in several RMS xenograft models except for an aggressive tumour cell line, RMS559. By searching for a direct target of the RMS core-regulatory transcription factor MYOD1, we identify another surface protein, CD276, as a potential target. Bicistronic CARs (BiCisCAR) targeting both FGFR4 and CD276, containing two distinct co-stimulatory domains, have superior prolonged persistent and invigorated anti-tumor activities compared to the optimized FGFR4-specific CAR and the other BiCisCAR with the same 4-1BB co-stimulatory domain. Our study thus lays down the proof-of-principle for a CAR T-cell therapy targeting both FGFR4 and CD276 in RMS. The success of Chimeric antigen receptor (CAR) T-cell therapy in solid tumours is hampered by the scarcity of suitable targets and suboptimal activation of the engineered T cells in the hostile microenvironment of the tumours. Here authors identify CD276 as target in childhood rhabdomyosarcoma, which, when combined into a bicistronic construct with a known target, FGF4R, allows enhanced tumour killing.